The significance of the changes that Sulla made to the Roman constitution, and to what extent these changes had been reversed by 70 B.C. (Groundings Undergraduate, 2010)
The time when Sulla rose to the dictatorship of the Roman Republic was one in which the power of the Senate was waning. On his accession Sulla implemented changes which sought to re-establish the authority of the Senate thus regaining stability within the state. Here I consider: the impact the reforms had on the existing Roman constitution; the reception of the reforms by different social groups; the political and social context surrounding their implementation and, where applicable, their reversal with the ultimate aim of establishing the reforms’ overall success in achieving the goals of their author.
Keywords: Roman Politics; Sulla; Sullan Reforms; Constitution; Rome; Senate; Legislation; Reversal; Repeal